Planned versus emergency cesarean delivery with previous one cesarean section: a prospective observational study - Sharma, Partha P.; Giri, Dipak K.; Bera, Surendra N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Women presents with previous history of cesarean section (CS) is a ‘high risk pregnancy’ and requires regular antenatal check-ups. Planned CS at term done for perinatal interest. Post cesarean pregnancy admitted through emergency required direct CS, for those not fit for vaginal birth as per different guidelines. Main objective of this study is to know neonatal and maternal outcome at term for planned versus emergency CS with previous one CS. Methods: Planned or emergency CS were done in 1003 pregnant women at term with previous one CS and outcome of both neonatal and maternal were noted. Emergency CS done in failed VBAC women were excluded from the study. Results: Planned CS before onset of labor were done in 22.93% and emergency CS in 77.07% in the present study. A significant number of women has undergone planned CS in cephalo-pelvic disproportion (45.21%), contracted pelvis (24.34%) and fetal growth restriction (6.95%) where P=0.000. Scar tenderness (20.18%), fetal distress (16.04%) and cephalo-pelvic disproportion (15.52%) were major indications for emergency CS. Maternal complications in the emergency CS group were pyrexia (P=0.000) and blood transfusion, required in 1.81% (P=0.000). There were two maternal death and hysterectomy required in 0.38% in the emergency CS compared to 1.30% in the planned CS (P=0.274). Neonatal complications were significant(P=0.018) in the emergency CS group. Common complications were jaundice (2.84% versus 1.73%, P=0.489), sepsis (0.25% versus 0.86%, P=0.487) and early neonatal death (2.97% versus 0.86%, P=0.119) in emergency CS compared to planned CS. Conclusions: Neonatal morbidity and mortality were significant in the emergency CS, compared to planned CS. Pyrexia and blood transfusion were significant maternal morbidity in the emergency CS group.